Organizational Justice and Organizational Citizenship Behavior: The Mediating Roles of Organizational Commitment and Leader Member Exchange - Hasyim, Aditya Fuad; Palupiningdyah, Palupiningdyah (Universitas Negeri Semarang, 2021)
This study aims to examine the effect of organizational justice on organizational citizenship behavior with organizational commitment and leader-member exchange as mediating variables for sewing employees of PT. Apparel One Indonesia 1. The sample used is 92 respondents with the sampling technique using purposive sampling. The data collection method used a questionnaire. Methods of data analysis using descriptive statistical tests with analysis tools, namely SmartPLS 3.0. The conclusion of this study is that organizational justice cannot improve organizational citizenship behavior either directly or through organizational commitment. However, organizational justice can increase organizational citizenship behavior only when through mediation of leader-member exchange. Recommendations for companies are that during the recruitment process, it is better to choose employees who are truly competent so that tasks can be distributed according to the employees' abilities. In addition, employees must be involved in every decision making so that employees will feel needed and recognized which in turn will bring out commitment to employees.